Why does the history of economic thought neglect Post-Keynesian economics?. (January 2020) - Guizzo, Danielle
Abstract : Despite receiving increased interest after the global financial crisis of 2007–2008 and consolidating itself as an established research program, Post-Keynesian economics remains under-represented within publications on the history of economics. When compared to other traditional heterodox approaches such as Marxist, Institutionalist, and Austrian economics, Post-Keynesian economics falls behind considerably, contradicting the Post-Keynesian appreciation for the history of the discipline. This article explores some reasons behind this detachment by considering two main factors: first, the recent disciplinary and institutional changes experienced by the history of economics in the last ten years; and, second, the recent 'maturing state' of Post-Keynesian economics and its unique treatment of the history of economic thought. The article concludes by suggesting a new research agenda for Post-Keynesianism, making use of the 'applied' turn proposed by the recent history of economic thought as one of the strategies for Post-Keynesians to engage with the economics discipline.